Perioperative Hyperglycemia is an Independent Risk Factor for Venous Thromboembolism Events After Operative Treatment of Geriatric Femur Fractures - Zachary J. Herman MD; Christopher J. Como MD; Romano Sebastiani BS; Ryan Gilbert BS; Audrey Chang BA; Gele B. Moloney MD (Geriatric Orthopaedic Surgery & Rehabilitation)
Introduction Geriatric femur fractures occur in complex hosts that pose significant challenges in perioperative management, with venous thromboembolism (VTE) as a well described complication. Hyperglycemia, prevalent in the perioperative period, has been implicated in increasing thrombotic risk. However, data on its impact on outcomes following femur fracture fixation in the elderly population remains limited. Methods A retrospective cohort analysis was conducted on adults >60 years old undergoing operative fixation for femur fractures between January 2017 and December 2019. Demographic information, comorbidities, and outcomes were collected from electronic medical records. Results Six hundred and fourteen patients met inclusion criteria. The average age was 78.7 years (30.3% male; 25.0% with diabetes mellitus (DM) diagnosis). Patients with postoperative glucose ≥180 mg/dL had significantly higher rates of pulmonary embolism (PE) and VTE within 90 days, and glucose ≥180 mg/dL was an independent predictor for these events. Those with a DM diagnosis had higher rates of sepsis but not PE, VTE, or other complications compared to those without DM. Conclusion Acute perioperative hyperglycemia, regardless of DM diagnosis, is an independent risk factor for VTE and PE following geriatric femur fracture fixation. Strict glucose control in the postoperative period may improve outcomes in this patient population.